2019
DOI: 10.1099/mic.0.000720
|View full text |Cite
|
Sign up to set email alerts
|

Proteins in the periplasmic space and outer membrane vesicles of Rhizobium etli CE3 grown in minimal medium are largely distinct and change with growth phase

Abstract: Rhizobium etli CE3 grown in succinate-ammonium minimal medium (MM) excreted outer membrane vesicles (OMVs) with diameters of 40 to 100 nm. Proteins from the OMVs and the periplasmic space were isolated from 6 and 24 h cultures and identified by proteome analysis. A total of 770 proteins were identified: 73.8 and 21.3 % of these occurred only in the periplasm and OMVs, respectively, and only 4.9 % were found in both locations. The majority of proteins found in either location were present only at 6 or 24 h: in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…The proteins with predicted transmembrane helices different from the short transmembrane helix in the N-terminus were excluded. These enrichment levels of periplasmic proteins are in line or above previous publications [21,22,23,24]. Undoubtedly, some extent of cell lysis occurred during preparation of periplasmic protein fractions, in that known cytoplasmic proteins were recovered, accounting for the 54.3% (Table S2).…”
Section: Resultssupporting
confidence: 90%
“…The proteins with predicted transmembrane helices different from the short transmembrane helix in the N-terminus were excluded. These enrichment levels of periplasmic proteins are in line or above previous publications [21,22,23,24]. Undoubtedly, some extent of cell lysis occurred during preparation of periplasmic protein fractions, in that known cytoplasmic proteins were recovered, accounting for the 54.3% (Table S2).…”
Section: Resultssupporting
confidence: 90%
“…As we have reviewed here, biochemical approaches are powerful tools for elucidating the composition, biogenesis, and function of MVs. Proteomic and lipidomic analyses indicate that the composition of MVs depends on the growth conditions (Choi et al, 2014;Kim et al, 2016;Wagner et al, 2018;Taboada et al, 2019), suggesting that the MVs are heterogenous and their functions differ depending on the environment. On the other hand, recent studies have shown different pathways of MV formation, which lead to different MV compositions.…”
Section: Resultsmentioning
confidence: 99%
“…One of the obstacles to progress in the field is a lack of standardized methodology in the isolation and purification of EVs, as well as a lack of well-defined identification of individual markers present on bacterial EVs [ 5 ]. EV composition and size can change drastically, depending on growth conditions [ 88 , 126 , 127 ] and on strains even within the same species [ 128 ].…”
Section: Conclusion and Perspectives: What We Have To Learn Regarding Bacterial Evsmentioning
confidence: 99%